Influence of Packaging and Storage Duration on Seed Quality of Wheat (Triticum aestivum L.) Varieties: Packaging and storage effects on wheat seed quality - Dhiman , Karam Chand; Kanwar, Rajesh; Kapila, Rakesh Kumar; Jyoti, Aparna; Thakur, Anubhav (Journal of Cereal Research, 2025)
An 18‑month study (April 2019–November 2020) investigated how packaging materials—specifically gunny bags versus high-density polyethylene (HDPE) bags—and storage duration affected several seed quality traits in two wheat varieties, WH 1105 and WH 1124. Researchers measured germination rate (%), vigor indiex I and II, field emergence (%), final plant stand, moisture content (%), and time to reach a 2 mm radicle length (hrs). Results showed that both packaging type and storage length and their interaction significantly impacted seed quality for both varieties. Notably, after 18 months in High density polyethylene  bags (HDPE), WH 1124 seeds exhibited superior performance compared to WH 1105, with higher first count (90.75%), germination (91.50%), vigor index I & II scores (2063.30 and 1294.75), field emergence (79.25%), and final plant stand (79.25%).